MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN MELALUI PERMAINAN ESTAFET BOLA DI TK SOSIAL WAGOLA - Siti Muna; La Jeti; Rachman Saleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine how ball relay games can improve gross motor skills in children aged 5-6 years at TK Sosial Wagola. Gross motor ability is an important developmental aspect that requires early stimulation; however, based on preliminary observation, children at TK Sosial Wagola still showed difficulties in body coordination, body control, and speed and agility. This study used a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted through pre-cycle, Cycle I, and Cycle II stages involving 10 children aged 5-6 years. Data were collected through observation, interviews, documentation, and field notes, then analyzed quantitatively using a percentage formula. The results showed that children's gross motor skills improved progressively, from 30.00% in the pre-cycle to 62.50% by the end of Cycle I, and reaching 95.00% in Cycle II, with all children achieving the Very Well Developed category. The most significant improvement occurred in the speed and agility indicator. This study concludes that ball relay games are effective in improving gross motor skills of children aged 5-6 years at TK Sosial Wagola.